Stigmasterol regulates microglial M1/M2 polarization via the TLR4/NF‐κB pathway to alleviate neuropathic pain - Si, Waimei; Li, Xin; Jing, Bei; Chang, Shiquan; Zheng, Yachun; Chen, Zhenni; Zhao, Guoping; Zhang, Di (Phytotherapy research, 2024)
(Switching from the microglial M1 phenotype to the M2 phenotype is a promising therapeutic strategy for neuropathic pain (NP). This study aimed to investigate the potential use of stigmasterol for treating NP. In animal experiments, 32 male Sprague–Dawley rats were randomly divided into the sham operation group, chronic constriction injury (CCI) group, CCI + ibuprofen group, and CCI + stigmasterol group. We performed behavioral tests, enzyme‐linked immunosorbent assay, hematoxylin‐esoin staining (H&E) staining and immunohistochemistry, immunofluorescence, and Western blotting. In cell experiments, we performed flow cytometry, immunofluorescence, Western blotting, and qRT‐PCR. Stigmasterol reduced thermal and mechanical hyperalgesia and serum IL‐1β and IL‐8 levels and increased serum IL‐4 and TGF‐β levels in CCI rats. Stigmasterol reduced IL‐1β, COX‐2, and TLR4 expression in the right sciatic nerve and IL‐1β expression in the spinal cord. Stigmasterol reduced the expression of Iba‐1, TLR4, MyD88, pNF‐κB, pP38 MAPK, pJNK, pERK, COX‐2, IL‐1β, and CD32 in the spinal cord of CCI rats while increasing the expression of IL‐10 and CD206. Stigmasterol decreased M1 polarization markers and increased M2 polarization markers in lipopolysaccharide (LPS)‐induced microglia and decreased the expression of Iba‐1, TLR4, MyD88, pNF‐κB, pP38 MAPK, pJNK, pERK, iNOS, COX‐2, and IL‐1β in LPS‐treated microglia while increasing the expression of Arg‐1 and IL‐10. Stigmasterol regulates microglial M1/M2 polarization via the TLR4/NF‐κB pathway to alleviate NP. Following peripheral nerve injury, microglia within the central nervous system undergo activation. This activation includes the presence of M1 microglia that secrete pro‐inflammatory cytokines, playing a crucial role in promoting neuroinflammation. To maintain an equilibrium within the inflammatory milieu, the presence of M2 microglia and the secretion of anti‐inflammatory cytokines are necessary for neuroprotection. Stigmasterol may regulate the M1/M2 polarization of microglia by targeting the TLR4/NF‐κB pathway, thereby effectively alleviating neuropathic pain.